Local Impedance Characterization for Scar and Fibrosis Detection: Towards a New Substrate Assessment for Atrial Mapping - Martínez Antón, Carmen (KIT Scientific Publishing, 2026)
Regions with pathologically altered substrate have been identified as proarrhythmic regions. Mapping techniques are currently used to estimate the location of these fibrotic areas. Local impedance has gained attention as another modality for atrial substrate assessment as it does not rely on the dynamically changing electrical activity of the heart. Simulations can help exploring the abilities of LI measurements to account for atrial substrate and be used as a surrogate for fibrosis detection.